Upaya Pemenuhan Hak dan Kewajiban Suami Istri Disabilitas - Rifai, Muhammad Agus; Husin Bawapi; Abdul Gafar Saidi (Institut Agama Islam (IAI) Faqih Asy'ari Kediri, 2024)
Rights and obligations arise from the practice of valid marriage. Therefore, each couple must fulfill their rights and obligations equitably. However, many couples struggle to perform these duties effectively due to various factors, including personal limitations that hinder their ability to meet their rights and obligations, often stemming from the incomplete or impaired functioning of one or more body parts. This research aims to explore the efforts made by disabled spouses to fulfill their rights and obligations and the impact of these efforts on family resilience. The study employs field research, utilizing an empirical approach and data collection techniques such as interviews and sampling. The findings indicate that the endeavors of disabled couples to fulfill their rights and obligations are remarkable. Husbands are willing to work hard to provide for their households, demonstrating care and commitment to family responsibilities. Meanwhile, wives also actively seek additional income and show obedience and respect towards their husbands. These efforts have positive implications for the resilience of their households.